Snakes of the Pantanal: biogeography and taxonomic, phylogenetic and ecomorphological diversity - Piatti, Liliana (2017)
Species composition in biological communities is a result of interactions of the evolutionary history of both organisms and environments, along with local factors that currently mediate species occurrence and coexistence. In floodplains, like the Pantanal, flood pulses are recognized as the main driver of ecological processes that control both species spatial and temporal distribution, but also shape communities. The Pantanal is the largest tropical floodplain on Earth and it has a less rich biota than that of surrounding regions. This has been attributed to the hardness imposed by the flood cycles on the organisms and also to the recent formation of the plain. The main goal of this thesis was to investigate diversity patterns of the snake community of the Pantanal regarding their origins, through stating and testing hypothesis about past and present processes that acted on the current assembly of snake communities in this seasonal floodplain. We adopted approaches that provided evidences for processes at deep and recent time scales, as well as a wide special scale, that encompasses the entire hydrographic basin where the Pantanal is located - the Paraguay River Basin. We found that Pantanal snake fauna belongs to a species group widely distributed in the basin, and is linked to the Paraguay River channel and nearby lowland areas. The entire basin has regionalized faunas distributed around the Pantanal floodplain, which may be acting as a barrier for some species and as a dispersal corridor for others. Our expectation that seasonal flooding could act as an environmental filter, allowing only species with adaptations to deal with this recurrent event to occur, was not supported. Rather than that, flooding seemed to be decreasing the relative force of deterministic processes on community assembly and so favoring species with generalist habits by promoting recurrent ecosystem disturbances. Environmental filter can be acting through the forest cover gradient, giving origin to richer communities in more open areas and assemblages formed by species with similar habitat uses in more forested areas. However, these patterns also could have originated from the ecological divergences between biotas originating from open and forested areas in South America